A flexible microprocessor system for the measurement of cell size. Issue 6 (June 1982) - Round, J M; Jones, D A; Edwards, R H
Abstract : A flexible system for the measurement of length and area is described. The system consists of the Reichert Jung MOP-1 area measuring device interfaced with a Commodore PET computer. Its use is illustrated by the planimetric measurement of cross sectional areas in histochemical preparations of normal and diseased muscle. While measurements are being made data can be displayed on the computer screen either in numerical form or as a frequency histogram together with simple statistical analyses. Hard copy can be obtained from an attached printer. Mean values for fibre area in normal human skeletal muscle are reported. An alternative, widely used method of calculating fibre area from the lesser diameter was found to give a consistent underestimate of approximately 30% when compared with our planimetric method. In diseased muscle with abnormally shaped fibres the discrepancy is even larger; such fibres can be identified using a "form factor" which relates the area of a cell to its perimeter. This rapid, accurate and flexible system is also suitable for the measurement of many different types of graphical record.